The Swiss "job miracle" - Michael Siegenthaler; Michael Graff; Massimo Mannino (ETH Zurich, KOF Swiss Economic Institute, 2014)
While Switzerland's recent growth of employment was high in historical and international perspective, the reasons for this "job miracle" were not well understood. As the "miracle" was not anticipated by economic forecasters, it consequently resulted in systematic and persistent forecast errors. This paper shows that the "miracle" is related to a substantial increase in the labor intensity of economic activity. To this end, we present a number of stylized facts reflecting shifts and structural changes that affected the Swiss economy around 2000. Then, we discuss potential drivers of the "miracle" which are consistent with these facts. Finally, we demonstrate how they contribute to understand why, during the last ten years, forecasters systematically underestimated the growth of domestic employment. Finally, we highlight that immigration was not only a consequence of the "miracle", but also an important cause, as it created additional jobs in Switzerland by raising local demand for goods and, most importantly, services.
Keywords: C52; E24; J21; J61; 330; Labor market; Swiss job miracle; employment forecasts; free movement of persons; migration; local multipliers